HUBUNGAN KUALITAS TIDUR DENGAN TEKANAN DARAH PADA SOPIR BUS DI TERMINAL KAMPUNG RAMBUTAN - Syaiful Anwar (2022)
Background: Hypertension is a fairly high health problem in the world. The occurrence of hypertension is an increase in systolic blood pressure exceeding 140 mmHg and diastolic blood pressure exceeding 90 mmHg on two measurements with a period of five minutes in a calm state. If the measured blood pressure always increases and is not detected as early as possible, coronary heart disease, kidney failure, and stroke can occur. Bus driver is a job that has a risk of increasing blood pressure, several factors increase blood pressure in bus drivers, namely the environment, lifestyle, physical activity, stress due to work pressure. Excessive stress due to physical activity and consuming stamina-boosting drinks, coffee and cigarettes can make his sleep uncomfortable which has an impact on the driver's sleep quality. Objective: The purpose of this study was to determine the relationship between sleep quality and blood pressure in bus drivers at the Kampung Rambutan Terminal. Methods: This research was a correlational study using cross sectional approach with a sample of 32 respondents. Data were collected for sleep quality using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and for blood pressure using a spynomanometer. Results: The results of the correlation test analysis using Spearman's rho with a significant value of p= 0.000 (p<0.05) which means that there is a relationship between sleep quality and blood pressure in bus drivers at Kampung Rambutan Terminal with a correlation coefficient value of 1,000 which means there is a strong relationship between the two variables. Conclusion: The conclusion obtained from this study is that there is a strong relationship between sleep quality and blood pressure in bus drivers at Kampung Rambutan Terminal.